Selected Poems - Ghose, Zulfikar, 1935- (Karachi Oxford University Press, 1991)
Pakistan inherits a rich tradition of social sciences and this selection of papers underlines the complex and diverse features of the Pakistan society.
Keywords: Indic Poetry (English) -- 20th Century -- Indic Poetry (English) -- English Poetry